Geographic differences in the prevalence of hypertension in Uganda: Results of a national epidemiological study. - Joseph Lunyera; Bruce Kirenga; John W Stanifer; Samuel Kasozi; Thys van der Molen; Wenceslaus Katagira; Moses R Kamya; Robert Kalyesubula (PLoS ONE)
Background Hypertension accounts for more than 212 million global disability-adjusted life-years, and more than 15 million in sub-Saharan Africa. Identifying factors underlying the escalating burden of hypertension in sub-Saharan Africa may inform delivery of targeted public health interventions. Methods As part of the cross-sectional nationally representative Uganda National Asthma Survey conducted in 2016, we measured blood pressure (BP) in the general population across five regions of Uganda. We defined hypertension as systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg, or on-going use of medications for the purpose of lowering BP among adults (≥18 years of age); pre-hypertension as systolic BP between 120 and 140 mmHg and/or diastolic BP bteween 80 and 90 mmHg among adolescents and adults (≥12 years of age). Findings Of 3416 participants who met inclusion criteria, 38.9% were male, and mean age ± SD was 33.8 ± 16.9 years. The age- and sex-adjusted prevalence of hypertension was 31.5% (95% confidence interval [CI] 30.2 to 32.8). The adjusted prevalence of hypertension was highest in the Central Region (34.3%; 95% CI 32.6 to 36.0), and it was comparable to that in the West and East Regions. However, compared with the Central Region, hypertension was significantly less prevalent in the North (22.0%; 95 CI 19.4 to 24.6) and West Nile Regions (24.1%; 95% CI 22.0 to 26.3). Adjustment for demographic characteristics (occupation, monthly income, and educational attainment) of participants did not account for the significantly lower prevalence of hypertension in the North and West Nile Regions. The prevalence of pre-hypertension was 38.8% (95% CI 37.7 to 39.8), and it was highly prevalent among young adults (21-40 years of age: 42.8%; 95% CI 41.2-44.5%) in all regions. Conclusions Hypertension is starkly prevalent in Uganda, and numerous more people, including young adults are at increased risk. The burden of hypertension is highest in the Central, Western, and Eastern regions of the country; demographic characteristics did not fully account for the disparate regional burden of hypertension. Future studies should explore the potential additional impact of epidemiological shifts, including diet and lifestyle changes, on the development of hypertension.